2019
DOI: 10.5539/ies.v12n5p120
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Knowledge Level of Teachers of Children with Autism Spectrum Disorder about the Importance of Applied Behavior Analysis (ABA) Strategies in Zarka City

Abstract: The current study aimed at assessing the knowledge level of teachers of children with Autism Spectrum Disorder about the Importance of Applied Behavior Analysis (ABA) strategies in Zarka City. Furthermore, the study attempted to explore whether teachers’ knowledge level differ according to their gender, years of experience, level of education, or specialized training. The sample of this study comprised of (60) teachers (25 male and 35 female). In order to achieve the goals of this study, the researcher constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 5 publications
4
13
0
3
Order By: Relevance
“…Training teachers in the principles and procedures of ABA is challenging because such training involves both academic knowledge of ABA and development of proficiency in actual implementation (Granpeesheh et al, 2010;Schloss & Smith, 1998). Thus, it is this lack of training and preparation that likely discourages special education teachers from implementing an ABA strategy (Schloss & Smith, 1998;Khaleel, 2019).…”
Section: Applied Behavior Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Training teachers in the principles and procedures of ABA is challenging because such training involves both academic knowledge of ABA and development of proficiency in actual implementation (Granpeesheh et al, 2010;Schloss & Smith, 1998). Thus, it is this lack of training and preparation that likely discourages special education teachers from implementing an ABA strategy (Schloss & Smith, 1998;Khaleel, 2019).…”
Section: Applied Behavior Analysismentioning
confidence: 99%
“…The sample included 120 special education teachers in private schools who teach students with ASD. A statistically significant difference in the result was found in total degrees of importance of using a variety of ABA practices among the participants due to receiving training previously (Khaleel, 2019). ABA practices found to be effective in improving students with ASD abilities and skills (Cooper et al, 2020;Khaleel, 2019;Makrygianni et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…12, No. 9;2019 type of system and/or prototype, this study concluded that the possible benefits of this type of technology are promising and that its use could help in the improvement of teaching, points out that its success or failure in the use of this device for educational purposes will depend to a large extent on the availability of applications that can be used with the device.…”
Section: Educatmentioning
confidence: 83%
“…The devices of this type that are more frequently used are Wii from Nintendo (Lee, 2008), MS-Kinect from Microsoft, and Sony's PS Move. Additionally, it is urgent to carry out training courses for professors on the applied behavior analysis strategies and their applications (Khaleel, 2019). 2017b), has aroused the interest of many researchers and developers who study the possible uses of said technology with a computer.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction with the software becomes simple for users because it is like they were in their daily environment [2]. On the other hand, there is an urgent need to train teachers to handle these types of applications, including topics on behavior analysis strategies [3], and their application in an educational context.…”
Section: Introductionmentioning
confidence: 99%